Test on the Reliability of the Subsurface Fault Geometry Estimated by Deformed River Terraces Along the Bailang River, North Front of the Qilian Shan (North West China) - Hu, Xiaofei; Ji, Xianghe; Cao, Xilin; Chen, Jiuying; Pan, Baotian (Frontiers in Earth Science, 2021)
The subsurface fault geometry is the base for understanding a process of crust deformation and mountain building. Based on kinematic models for fault-related folds, a geomorphic method is recently applied to estimate the subsurface fault geometry, while the validation on its reliability is lacking. In this study, we surveyed a suit of river terrace surfaces across an active fold at the north front of the Qilian Shan. According to the deformation geometry of the terraces, the fold deformation is interpreted by a listric fault fold model, and based on this kinematic model, the fault geometry underlying the fold is estimated. In comparison between the estimated fault geometry and a seismic reflection profile, we found that the decollement depth and the back thrust are highly consistent with each other. Although some small fault bends or internal shearing cannot be estimated solely by the terrace deformation, the overall fault geometry is successfully revealed by the terrace deformation. Using this fault geometry and the terrace dating results, the region deformation kinematics are re-evaluated, which suggest that the dip slip (in a rate of 1.8 ± 0.4 mm/a) along the decollement is mainly accommodated by two structures, one is the blind-back-thrust fault within the piggy basin in a dip-slip rate of 0.9 ± 0.3 mm/a and another is the thrust and fold at the west portion of the Yumu Shan range.